2009
DOI: 10.1007/s10562-009-0163-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Silica Supported Nickel Catalyst for Methanation with Improved Activity by Room Temperature Plasma Treatment

Abstract: Room temperature glow discharge plasma was applied to treat the nickel precursor supported on SiO 2 . According to the catalyst characterization, the calcination thermally of the plasma treated sample shows small particle size and high dispersion. Such prepared sample presents high conversions of carbon monoxide and hydrogen for the reaction of methanation with a significantly improved anticarbon deposition performance. The plasma-treated sample shows enhanced metal-support interaction and keeps good dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…A typical property of these kinds of plasma is that electrons in nonthermal plasma can reach temperatures of 10,000-100,000 K (1-10 eV) while the gas temperatures remain as low as room temperature [9]. Liu et al [10][11][12][13] showed that Ni(NO 3 ) 2 , Fe(NO 3 ) 3 , and Co(NO 3 ) 2 were decomposed by argon glow discharge plasma. Chu et al [14,15] have recently prepared alumina-and silica-supported Co catalysts using glow discharge plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical property of these kinds of plasma is that electrons in nonthermal plasma can reach temperatures of 10,000-100,000 K (1-10 eV) while the gas temperatures remain as low as room temperature [9]. Liu et al [10][11][12][13] showed that Ni(NO 3 ) 2 , Fe(NO 3 ) 3 , and Co(NO 3 ) 2 were decomposed by argon glow discharge plasma. Chu et al [14,15] have recently prepared alumina-and silica-supported Co catalysts using glow discharge plasma.…”
Section: Introductionmentioning
confidence: 99%
“…However, glow discharge plasma is generally operated under low-pressure conditions in a vacuum system. Decomposition of the supported nitrate using glow discharge plasma requires approximately 1-2 h [13,14] and usually assists in the calcination process to increase the stability of the catalyst [10,15]. In contrast, dielectric-barrier discharge (DBD) plasma can be initiated under atmospheric conditions with a high density and more high-energy electrons.…”
Section: Introductionmentioning
confidence: 99%
“…The same procedure as the second step was used. The Ni/SiO 2 was prepared using a conventional impregnation method as reported earlier [30]. The loading of nickel in Ni@SiO 2 and Ni/SiO 2 catalysts is the same, both are 10 wt %.…”
Section: Preparation Of Ni/sio 2 Catalystmentioning
confidence: 99%
“…Ru-based catalysts retain the best active for syngas methanation, but limited resource and high cost restrict their large-scale commercialization 6-8 . Ni-based catalysts have been widely used for their low cost, high catalytic activity and selectivity for methane [9][10][11] . In recent decades, great efforts have been made to produce high-effi ciency catalysts retaining high activity at low-temperature (ca.…”
Section: Introductionmentioning
confidence: 99%